IDENTITY VERSUS IDENTITY CONFUSION IN ADOLESCENT LIFE - Iana CIOBANU (Moldova State University, 2018)
Transformations that occur throughout the teenager's personality structure have particularly important implications: Physiological maturation, the development of the ability to know, the emergence of new desires and feelings are treated in this article. These give the teenager the impression that he is a totally new person, different from the child that was until recently. Abandoning the old identity sometimes creates the feeling of void, lack of landmarks and disorientation. In order to balance and rediscover himself, he seeks new identifications, new patterns of personality to relate to. Thus, the teenager gradually becomes aware not only of what he is, but also of what he can become. IDENTITATE VERSUS CONFUZIE DE IDENTITATE ÎN VIAȚA ADOLESCENULUI În articol sunt abordate transformările care se produc în întreaga structură a personalităţii adolescentului și care au implicaţii deosebit de importante: maturizarea fiziologică, dezvoltarea capacităţii de cunoaştere, apariţia de noi dorinţe şi sentimente. Acestea formează la adolescent impresia că este o persoană cu totul nouă, diferită de copilul care era până de curând. Abandonarea vechii identităţi creează uneori sentimentul de vid, lipsă de repere şi dezorientare. Pentru a se echilibra şi a se redescoperi pe sine însuşi el caută noi identificări, noi modele de personalitate la care să se raporteze. Astfel, adolescentul devine treptat conştient nu doar de ceea ce este, ci şi de ceea ce poate deveni.